Control of the Magnetic Properties of a Magnetic Field Guidable Biocompatible Nanovehicle. (19th August 2016) - Granitzer, Petra; Rumpf, Klemens; Reissner, Michael; Poelt, Peter
Abstract : Within this work a biocompatible magnetic nanovehicle which is movable in aqueous solutions by a magnetic field is presented. The nanovehicle consists of a porous silicon template and encapsulated iron oxide nanostructures. Both materials employed, porous silicon (PSi) as well as iron oxide are known to be biocompatible. Two routes are employed to produce various iron oxide phases of the embedded nanostructures within PSi. On the one hand, readily synthesized magnetite nanoparticles (NPs) which are superparamagnetic (SPM) due to their size, are infiltrated into the pores. On the other hand chemical deposition of iron oxide inside the PSi templates is used. Mainly the synthesis of the nanocomposite as well as the magnetic properties of the systems will be discussed.